PENGARUH METODE GASING Vs METODE TRADISIONAL DAN MOTIVASI BELAJAR TERHADAP PRESTASI BELAJAR MATEMATIKA MURID KELAS TINGGI DI SD NEGERI INPRES MALOMPO NABIRE: PENGARUH METODE GASING Vs METODE TRADISIONAL DAN MOTIVASI BELAJAR TERHADAP PRESTASI BELAJAR MATEMATIKA MURID KELAS TINGGI DI SD NEGERI INPRES MALOMPO NABIRE - wilyam; Nurmida Catherine Sitompul; Agung Pramujiono (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the effect of the GASING method compared to traditional methods and the effect of learning motivation on student achievement at SD Negeri Inpres Malompo Nabire. The method used was a quasi-experimental with a 2×2 factorial design, involving 60 students selected through purposive sampling. The instruments used were a learning achievement test and a learning motivation questionnaire. The results of the Two-Way ANOVA analysis showed that the GASING method was more effective than the traditional method (F = 13.413; p = 0.001), but learning motivation also had a significant effect on student achievement (F = 4.935; p = 0.030). In addition, there was a significant interaction between learning methods and learning motivation (F = 10.647; p = 0.002), where the GASING method was more effective on students with low motivation. Conversely, students with high motivation tended to have better achievement with other learning methods. The conclusion of this study is that both learning methods and learning motivation influence student academic achievement. Therefore, it is important for teachers to consider students' motivational characteristics in choosing the right learning method, such as implementing the GASING method